Pre-school teacher's attitudes towards inclusion of children with develomental needs in Kindergartens in Singapore - Nonis, Karen; Chong, W.; Moore, D.; Tang, H.; Koh, P. (International Journal of Special Education, 2016)
Including children with learning difficulties and disabilities in regular classrooms continues to be a challenge for teachers. This study investigated the perceptions of kindergarten teachers and learning support educators (LSEd) towards including children with developmental needs and or learning difficulties in pre-schools in Singapore. A total of 50 participants responded to a survey questionnaire and a group interview session. The study concluded that that the teachers were positive towards including children with developmental learning needs into regular kindergartens. This paper provides insights into the concerns of pre-school teachers about training and support that at the time of conducting the research was much needed in the pre-school sector.